Alexander the Great and Bactria : the formation of a Greek frontier in central Asia - Holt, Frank Lee. (Mnemosyne, Supplements, 1995)
The creation of a Greek Frontier in Central Asia was one of the most famous and far-reaching achievements of Alexander the Great. Yet the process was shaped as much by the political traditions of the natives as by the cultural traditions of the newcomers. This book examines this key historical clash from both sides, and shows that the birth of Hellenistic Bactria was a traumatic one eliciting more bitterness than 'brotherhood'. The book is composed of four major parts: Part I provides an introduction to both Bactrian and Alexander studies; Part II surveys the land and peoples of Central Asia prior to Alexander's 'conquest'; Part III covers the Graeco-Macedonian invasion and the effects of colonization; Part IV treats the aftermath, from the death of Alexander to the accession of Seleucus.